Etika Penyelidikan Islam: Satu Analisa - Abd. Rahim, Rahimin Affandi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
Basically, this work was focused upon the three different aspects about the prerequisition of the Islamic research. First, it will highlight upon the definition of Islamic research, following by the second section which displayed the significance of the Islamic research in the academia world. Finally in the third section, special attention will be given to the substances as well as the classical and modern knowledge that need to be fulfilled by the Muslim researcher.